Dopaminergic Neuronal Differentiation from the Forebrain-Derived Human Neural Stem Cells Induced in Cultures by Using a Combination of BMP-7 and Pramipexole with Growth Factors - Yang, HongNa; Wang, Jing; Wang, Feng; Liu, XiaoDun; Chen, Heng; Duan, WeiMing; Qu, TingYu (Frontiers in Neural Circuits, 2016)
Transplantation of dopaminergic (DA) neurons is considered to be the most promising therapeutic strategy for replacing degenerated dopamine cells in the midbrain of Parkinson’s disease (PD), thereby restoring normal neural circuit function and slow clinical progression of the disease. Human neural stem cells (hNSCs) derived from fetal forebrain are thought to be the important cell sources for producing DA neurons because of their multipotency for differentiation and long-term expansion property in cultures. However, low DA differentiation of the forebrain-derived hNSCs limited their therapeutic potential in PD. In the current study, we explored a combined application of Pramipexole (PRX), bone morphogenetic proteins 7 (BMP-7), and growth factors, including acidic fibroblast factor (aFGF), forskolin, and phorbol-12-myristae-13-acetate (TPA), to induce differentiation of forebrain-derived hNSCs towards DA neurons in cultures. We found that DA neuron-associated genes, including Nurr1, Neurogenin2 (Ngn2), and tyrosine hydroxylase (TH) were significantly increased after 24h of differentiation by RT-PCR analysis (p<0.01). Fluorescent examination showed that about 25% of cells became TH-positive neurons at 24h, about 5% of cells became VMAT2 (vascular monoamine transporter 2)-positive neurons, and less than 5% of cells became DAT (dopamine transporter)-positive neurons at 72h following differentiation in cultures. Importantly, these TH-， VMAT2- and DAT-expressing neurons were able to release dopamine into cultures under both of the basal and evoked conditions. Dopamine levels released by DA neurons produced using our protocol were significantly higher compared to the control groups (P<0.01), as examined by ELISA. Our results demonstrated that the combination of PRX, BMP-7, and growth factors was able to greatly promote differentiation of the forebrain-derived hNSCs into DA-releasing neurons.